Analisis Gambaran Pengetahuan dan Psikologi Penderita Diabetes Mellitus di Kota Jambi - Yesni, Marnila; Ramadhani, Dwi Yunita; Maimaznah, Maimaznah; Febrianti, Dwi Kartika; Yanti, Rahmi Dwi; Yuliana, Yuliana; Rino, Rino; Alfajri, Jufri; Suri, Marta (Jurnal Akademika Baiturrahim Jambi, 2025)
Diabetes mellitus is a group of metabolic disorders characterized by increased blood glucose levels (hyperglycemia) resulting from defects in the insulin system, insulin action, or both. Where it has increased every year and is of course a special concern for patients with diabetes mellitus. Diabetes Mellitus is a chronic disease that has a negative impact on the physical and psychological sufferers, physical disorders that occur such as polyuria, polydipsia, polyphagia, complaining of fatigue and drowsiness. The city of Jambi with this research design is a quantitative research with a descriptive method with a research population of 10,233 and a sample size of 82 people. The results showed that 56.1% had a good level of knowledge and 44.9% had sufficient knowledge about diabetes mellitus. 51.3% of respondents experienced mild anxiety and 2.4% experienced moderate anxiety. 18.3% of respondents experienced mild stress. 23.1% of respondents experienced mild depression and 1.3% experienced moderate depression. The need to pay attention and look for psychological solutions related to diabetes mellitus.